Jurisdictional Fragmentation and Sprawl - Oskari Harjunen; Eetu Kauria; Tuukka Saarimaa; Janne Tukiainen (Helsinki Graduate School of Economics, 2024)
This paper explores the connection between jurisdictional fragmentation and sprawl. We utilize Finnish municipal mergers as a quasi-experiment which induces exogenous variation in the number of local jurisdictions in a given area. We are able to draw on rich register data providing granular location information for the full population of Finnish residents. We compare the location of new buildings (and their residents) in the actual mergers to the location of new buildings in a control group of hypothetical mergers simulated from the premerger municipality map in a difference-in-differences framework. When using our full sample, we do not find statistically significant effects on the location of newly constructed residential buildings. However, in smaller municipalities new single-family and row houses were built about 10% or 2 km closer to the new administrative center. These effects materialize after two full council terms or roughly ten years and are driven by mergers that resemble functional urban areas.
Keywords: H70; R31; R52; 330; jurisdictional fragmentation; sprawl; municipality mergers